Proteome-Wide Analysis of Lysine 2-Hydroxyisobutyrylation in Aspergillus niger in Peanuts - Xu, Manlin; Zhang, Xia; Yu, Jing; Guo, Zhiqing; Li, Ying; Song, Xinying; He, Kang; Li, Guowei; Chi, Yucheng (Frontiers in Microbiology, 2021)
Aspergillus niger is a very destructive pathogen causing severe peanut root rot, especially in the seeding stage of peanuts (Arachis hypogaea), and often leading to the death of the plant. Protein lysine 2-hydroxyisobutyrylation (Khib) is a newly detected post-translational modification identified in several species. In this study, we identified 5041 Khib sites on 1453 modified proteins in A. niger. Compared with five other species, A. niger has conserved and novel proteins. Bioinformatics analysis showed that Khib proteins are widely distributed in A. niger and are involved in many biological processes. GO and KEGG enrichment analyses revealed that Khib proteins were significantly enriched in many cellular compartments and pathways, such as ribosomes and proteasome subunits. A total of 223 Khib proteins were part of the PPI network, thus, suggesting that Khib proteins are associated with a large range of protein interactions and diverse pathways in the life processes of A. niger. Several identified proteins are involved in pathogenesis regulation. Our research provides the first comprehensive report of Khib and an extensive database for potential functional studies on Khib proteins in this economically important fungus.